ASSOCIATION OF INTERNAL ASSESSMENT WITH FINAL RESULT OF SECOND PROFESSIONAL MBBS EXAMINATION - Muhammad Alamgir Khan (Army Medical College Rawalpindi, 2019)
Objective: To explore whether the performance of a 2nd year MBBS student in subject of physiology by continuous assessment method as determined by internal assessment correlates to the final summative evaluation in 2nd professional examination.